Gambaran Pengetahuan Wanita Usia Subur Tentang Metode Kontrasepsi Jangka Panjang di Wilayah Kerja Puskesmas Punggur - Ely Elrmawati; Fatya Nurul Hanifa; Indah Purnamasari (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Background: Long-term contraceptive method (MKJP) is a contraceptive tool used to delay, space pregnancies and even control fertility by reducing fertility used in the long term. Factors behind the low use of MKJP in WUS are concerns related to long-term fertility disorders, side effects, disapproval from husbands and lack of knowledge and access to information. The purpose of this study was to determine the description of knowledge of women of childbearing age about long-term contraceptive methods in the working area of ​​Punggur Health Center. Research Methods: The research design in this study is descriptive research with a survey approach with the Sovin formula. The number of samples is 101 WUS. Univariate data analysis with a frequency distribution table. Results: Knowledge based on age, the highest frequency is 20-35 years old, as many as 68 people (67.3%), knowledge based on education, the highest frequency distribution of respondents is high school education, as many as 63 people (62.4%), knowledge based on occupation, the highest frequency distribution of respondents is housewife, as many as 52 people (51.5%) and knowledge based on income, the highest frequency distribution of respondents is <UMR (Rp. 2,878,286). The highest knowledge of women of childbearing age is poor knowledge of 46 people (45.5%) and the lowest is good knowledge of 12 people (11.9%). Conclusion: The highest knowledge of women of childbearing age is poor knowledge of 46 people (45.5%).